Genome‐wide diversity analysis suggests divergence among Upper Guinea and the Dahomey Gap populations of the Sisrè berry (Syn: miracle fruit) plant (Synsepalum dulcificum [Schumach. & Thonn.] Daniell) in West Africa - Dèdéou A. Tchokponhoué; Enoch G. Achigan‐Dako; N'Danikou Sognigbé; Daniel Nyadanu; Iago Hale; Alfred O. Odindo; Julia Sibiya (The Plant Genome, 2023)
Abstract Although Synsepalum dulcificum is viewed as one of the most economically promising orphan tree crops worldwide, its genetic improvement and sustainable conservation are hindered by a lack of understanding of its evolutionary history and current population structure. Here, we report for the first time the application of genome‐wide single nucleotide polymorphism genotyping to a diverse panel of S. dulcificum accessions to depict the genetic diversity and population structure of the species in the Dahomey Gap (DG) and Upper Guinea (UG) regions to infer its evolutionary history. Our findings suggest low overall genetic diversity but strong population divergence within the species. Neighbor‐joining analysis detected two genetic groups in the UG and DG regions, while STRUCTURE distinguished three genetic groups, corresponding to the UG, Western DG, and Central DG regions. Application of Monmonier's algorithm revealed the existence of a barrier disrupting connectivity between the UG and DG groups. The Western DG group consistently exhibited the highest levels of nucleotide and haplotype diversities, while that of the Central DG exhibited the lowest. Analyses of Tajima's D, Fu's Fs, and Achaz Y* statistics suggest that while both UG and Central DG groups likely experienced recent expansions, the Western DG group is at equilibrium. These findings suggest a geographical structuring of genetic variation which supports the conclusion of differential evolutionary histories among West African groups of S. dulcificum. These results provide foundational insights to guide informed breeding population development and design sustainable conservation strategies for this species.